Varicella Zoster in pregnancy. (March 2021) - Nanthakumar, Meenu Priyadarshini; Sood, Akanksha; Ahmed, Maimoona; Gupta, Janesh
Abstract: Chickenpox during pregnancy can cause serious complications for both mother and fetus. This includes varicella pneumonia in the mother, fetal varicella syndrome and varicella of newborn. Primary prevention includes vaccination against varicella infection and is part of standard childhood immunisation programme in many countries. Timely post-exposure prophylaxis of susceptible pregnant women with varicella zoster immunoglobulin is key to preventing chickenpox during pregnancy and its adverse fetomaternal sequelae. Antiviral therapy and appropriate supportive treatment improve maternal and neonatal outcomes